Religion, power, and illusion: a genealogy of religious belief - Hurley, Patrick J. (Prometheus, 2022)
"Religion, Power & Illusion: A Genealogy of Religious Belief puts forth the idea that modern concepts of God are inextricably tied to the generations of mortal priests that shaped biblical and religious ideas"--